Case Report: An endogenous endophthalmitis case caused by Haemophilus influenzae - Tsai, Chia Hsuan; Liu, Li-Teh; Hsu, En Chi; Sung, Shao-Yu; Tsai, Jih-Jin (Frontiers in Medicine, 2025)
Haemophilus influenzae is a bacterium that typically colonizes the human respiratory tract. However, it can also infect the eyes, potentially leading to endophthalmitis. The general prognosis of endophthalmitis is often poor, frequently resulting in decreased visual acuity. We present the case of a 71-year-old male who experienced sudden blurring of vision, pain, and a significant hypopyon in the fundus of his right eye resulting from Haemophilus influenzae. According to previous reports, many cases of Haemophilus influenzae endophthalmitis have poor outcomes, often resulting in permanent visual impairment. However, the patient achieved an excellent prognosis in our case due to prompt diagnosis and emergent treatment.